Multifunctional effect of carbon matrix with sulfur dopant inspires mixed metal sulfide as freestanding anode in sodium-ion batteries - Zhang, Peilin (2025)
As active materials for large-radius Na+ storage, metal sulfide (MS) anodes still face several challenges, including poor intrinsic electric conductivity, severe volume change along with the shuttle and dissolution effects of discharge-produced polysulfides. In this work, the mixed nickel-manganese sulfides (NiMnS) in the morphology of uniform 2D ultrathin nanosheets are derived from layered metal-organic frameworks (MOFs), where the NiS-MnS heterojunction are accommodated in carbon matrix with S dopant (NiMnS/SC). Through experiments and density functional theory (DFT) simulations, it is revealed that the carbon matrix with S dopant has multifunctional effects on active NiMnS during the charge/discharge process, including conductive intermediary, electrochemical active site, physical barrier, and chemical adsorption. This work may promote the design of MS-based electrodes in SIBs and extend the application of carbon material with S dopant in Na-S batteries.